Undergraduate Business Education E-Learning Delivery in Covid-19 Pandemic Era - Nwadiani, Comfort O.; Egbri, J. N. (NIU Journal of Humanities; Vol 7 No 1 (2022): NIU Journal of Humanities, Vol. 7 No. 1, March 2022DO - 10.58709/niujhu.v7i1.1387, 2022)
E-learning is the process of utilizing electronic technologies and resources to access teaching and learning with or without physical classroom.  This paper examined how business education students access e-learning in covid-19 era. The historical development of covid-19 with its various variants, concept of business education and business education delivery before the covid-19 pandemic era. process of e-learning permit accessibility to learning with physical infrastructure and does not require face to face contact between the teacher and learners irrespective of the distance The state of the business education classrooms before and after the covid-19 pandemic, students, teacher and institutions preparedness were equally discussed and teacher.  Historical method was adopted for this study. Vital documents and literature were utilized in the course of the study. The paper concluded that even though there are numerous advantages associated with the adoption of e-learning in business education programme, several issues that need to be addressed and put in place to achieve the maximum benefits. It was recommended that stake holders in education should provide facilities such as good and strong internet, stable electricity, and good working computers among others for students, teachers and institutions to be able to teaching and learning using e-learning delivery. Keywords: E-Learning Delivery, Covid-19 and Pandemic Era